(untitled) (BIS Humanities and Social Science, 2025)
Converts often need help with challenges, such as a lack of understanding of Islamic teachings, social pressure, and difficulty building social relationships. Effective coaching is critical in helping converts overcome these challenges. However, this coaching process often faces various obstacles, such as the lack of communication intensity between coaches and converts and the lack of confidence. This research aims to find effective communication patterns in the coaching of Mualaf Daratan Maju Kuat Mandiri (Muda Mukadiri) in Yogyakarta. The method used in this research is descriptive qualitative. Data collection techniques through in-depth interviews and observation. The data validity test technique uses source triangulation. Data analysis techniques in this study include data collection, reduction, presentation, and conclusion drawing. The results showed that the communication patterns used in the coaching of Muda Makudiri convert are top-down communication patterns when the coach delivers the coaching, bottom-up communication patterns when converts respond to the coaching material and informal communication that occurs outside the coaching activities. Muda Makudiri also has a WhatsApp group where coaches and converts can share information about various converts’ activities. This research implies the need for openness and confidence of converts so that communication can run effectively.